PERANCANGAN BOARDING SCHOOL DI KOTA PONTIANAK DENGAN PENDEKATAN ARSITEKTUR TROPIS - Fernando Redondo Gultom; Muhammad Nurhamsyah; Irwin Irwin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
Poverty is one of the many problems that exist in Indonesia. Based on the data, one of the causes of poverty is the low level of education of an individual so that they do not have sufficient productivity to carry out a business or job. The level of education is an indicator that determines the level of the Human Development Index (IPM) in a region. West Kalimantan Province is one of the areas with a low HDI level in Indonesia. In an effort to increase the HDI in the province of West Kalimantan, it is necessary to have a place to accommodate underprivileged children who want to go to school. The boarding school system can be an appropriate alternative that not only provides learning opportunities but also self-development for students. Actors in boarding schools live and carry out activities fully in the school environment so that they help pay attention to character growth, children's health, and can also ease the burden on family life. The design of the boarding school uses the glassbox (rational) method where data collection and analysis forms the basis before creating a work that is logical and in accordance with its function. The location of the boarding school design is located in an area that has a tropical climate. In designing a boarding school using a tropical architectural approach. The application of tropical architecture in boarding schools is expected to be able to solve various problems that are owned by tropical climate areas so that the relationship between the environment and buildings and user activities in buildings can run optimally.